2011
DOI: 10.1016/j.jcss.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Balanced energy allocation scheme for a solar-powered sensor system and its effects on network-wide performance

Abstract: Solar power can extend the lifetime of wireless sensor networks (WSNs), but it is a very variable energy source. In many applications for WSNs, however, it is often preferred to operate at a constant quality level rather than to change application behavior frequently. Therefore, a solar-powered node is required adaptation to a highly varying energy supply. Reconciling a varying supply with a fixed demand requires a good prediction of that supply, so that demand can be regulated accordingly. We describe two ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…The solution proposed by Noh and Kang [94] is similar to previous approaches. They use the EWMA equation to keep track of the solar energy profile observed in the past.…”
Section: Prediction Modelsmentioning
confidence: 76%
“…The solution proposed by Noh and Kang [94] is similar to previous approaches. They use the EWMA equation to keep track of the solar energy profile observed in the past.…”
Section: Prediction Modelsmentioning
confidence: 76%
“…Noh et al showed how to use solar energy to maximize the amount of throughput by adaptively controlling the reliability [15]. In addition, they designed simple solar energy allocation (SSEA) and accurate solar energy allocation (ASEA) algorithms to optimally utilize the periodically harvested solar energy, while minimizing the variability of energy allocation [16]. Chen et al investigated the problem of maximizing the throughput over a finite-horizon time period and proposed a three-step approach to solve the problem [17].…”
Section: Related Workmentioning
confidence: 99%
“…Denote by B i,t the remaining energy of sensor node i at slot t. Let ρ i,t and A i,t denote the total amount of harvested energy and energy allocation for sensor node i at slot t, respectively. It is shown in [16] [20] that the sensor nodes can estimate ρ i,t with high accuracy. Their results will be introduced in this paper to estimate ρ i,t .…”
Section: Network Model and Problem Statementmentioning
confidence: 99%
“…Copyright is held by the owner/author(s). works have proposed energy predictions methods for energyharvesting WSNs (EH-WSNs) [1,4,5,3]. In this work, we propose a simple yet effective enhancement of the ProEnergy prediction algorithm [1] to improve the accuracy of solar energy predictions, while, at the same time, reducing its memory and energy overhead.…”
Section: Introductionmentioning
confidence: 99%